PCR detection of staphylococcal enterotoxin genes in Staphylococcus aureus strains isolated from raw and pasteurized milk - Rall, V. L. M. [UNESP]; Vieira, F. P. [UNESP]; Rall, R.; Vietis, R. L. [UNESP]; Fernandes, A. [UNESP]; Candeias, J. M. G. [UNESP]; Cardoso, K. F. G. [UNESP]; Araujo, J. P. [UNESP] (Elsevier B.V., 2008)
Milk is considered a nutritious food because it contains several important nutrients including proteins and vitamins. Conversely, it can be a vehicle for several pathogenic bacteria such as Staphylococcus aureus. This study aimed to analyze the frequency of genes encoding the staphylococcal enterotoxins (SEs) SEA, SEB, SEC, SED, SEE, SEG, SEH, SEI and SEJ in S. aureus strains isolated from raw or pasteurized bovine milk. S. aureus was found in 38 (70.4%) out of 54 raw milk samples at concentrations of up to 8.9 X 10(5) CFU/ml. This microorganism was present in eight samples of pasteurized milk before the expiration date and in 11 samples analyzed on the expiration date. of the 57 strains studied, 68.4% were positive for one or more genes encoding the enterotoxins, and 12 different genotypes were identified. The gene coding for enterotoxin A, sea, was the most frequent ( 16 strains, 41%), followed by sec (8 strains, 20.5%), sed (5 strains, 12.8%). seb (3 strains. 7.7%) and see (2 strains, 5.1%). Among the genes encoding the other enterotoxins, seg was the most frequently observed (11 strains. 28.2%), followed by sei (10 strains) and seh and sej (3 strains each). With the recent identification of new SEs, the perceived frequency of enterotoxigenic strains has increased. suggesting that the pathogenic potential of staphylococci may be higher than previously thoughts however, further studies are required to assess the expression of these new SEs by S. aureus. and their impact in foodborne disease. The quality of Brazilian milk is still low. and efforts from the government and the entire productive chain are required to attain consumer safety. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: S. aureus; Staphylococcal enterotoxins; Raw milk